The Effect Of Peer-Assisted Learning (PAL) Method On Visual Programming Knowledge Outcomes In Educational Technology Students - Dian Franssischa Kusumaningsih; Yerry Soepriyanto; Fikri Aulia (Green Publisher Indonesia, 2024)
This study aims to evaluate the effect of the Peer-Assisted Learning (PAL) method on differences in student knowledge outcomes in the Visual Programming course in the Educational Technology Study Program. This study used a quasi-experimental design with two groups, namely the experimental class that applied the PAL method vertically and the control class that used conventional learning methods. The research participants totaled 50 students, drawn from the four class offerings randomly and divided into 2 class groups of 25 learners each. Data were collected through learning motivation questionnaire and knowledge test measured by Likert scale and Bloom's Taxonomy-based test on cognitive domain. Results of statistical analysis with Two-Way Anova test showed that there was no significant difference in knowledge outcomes with a value of 0.331>0.05 based on learning motivation. However, the study showed a value of 0.036 <0.05, meaning that there was a significant difference between the PAL method and conventional learning on student knowledge outcomes. In addition, the value of 0.972>0.05 means that there is no significant interaction between the level of student learning motivation and learning methods on knowledge outcomes. This study found good responses from students where they prefer and are enthusiastic about learning with the PAL method compared to the conventional method, because the method is considered more flexible and comfortable to use for learning. This study suggests further evaluation related to the use of the PAL method by improving tutor skills and setting the duration of learning to increase effectiveness in achieving student learning outcomes